AN OVERVIEW OF PERTUSSIS REEMERGENCE AND EVIDENCE OF ITS RESURGENCE IN BRAZIL - Silva, Flávio Rocha da; Navarro, Marli Brito M. de Albuquerque; Pinto, Luiz André L.T.; De-Simone, Salvatore Giovanni (Revista de Patologia Tropical / Journal of Tropical Pathology, 2014)
About two thousand cases of pertussis are reported in Brazil each year, with the highest incidence and mortality rates occurring in children under one year old. The disease is becoming common in Brazil; however the state of Rio de Janeiro has been showing low reporting figures in relation to other states in the Southeast region. This research work aimed to evaluate the difficulties faced by medical teams when confirming suspect cases of pertussis in healthcare units throughout the state of Rio de Janeiro and to use available data to confirm pertussis diagnosis within the last two years. Epidemiological surveys were conducted among medical personnel from healthcare units who presented the main obstacles to confirming suspect cases. Results show that a lack of laboratory diagnosis, poor differential diagnosis, low knowledge of the disease and a lack of clinical experience are, among other factors, relevant to the low reporting rates in the region.